(untitled) (Research, Society and Development, 2024)
The objective of this work was to carry out a case study about the anomalous lingual frenulum in infants, exposing the consequences of such an anomaly, means for diagnosis, most viable treatment and its results. The methodology was developed through a clinical case report associated with research into scientific articles in order to support the study and enrich this present work. This anomaly interferes with tongue movements during lalation, crying and sucking, which can cause discomfort during breastfeeding and affect the child’s weight. It is necessary to emphasize that the complete or partial fusion of the tongue on the floor of the mouth is called ankyloglossia, and frenotomy is a procedure considered to be very effective in these cases. Frenotomy is a minimally invasive technique, with the expectation of mild postoperative pain or, in some cases, no pain, and provides immediate results. In the case in question, a one-month-old male baby was evaluated at the Dental Clinic of the Tiradentes University, where after taking an anamnesis, clinical examination and tongue test, he was diagnosed with ankyloglossia and the chosen treatment was frenotomy. Shortly after performing the technique, there were significant improvements in stomatognathic functions, mobility and posture of the tongue. Therefore, it is concluded that an efficient diagnosis and intervention in the first months of life make all the difference in the child’s life.